Impact of COVID-19 Lockdown on Physical Activity in a Sample of Greek Adults - Dimitrios I. Bourdas; Emmanouil D. Zacharakis (MDPI AG, 2020)
It is well known that physical inactivity increases the risk of global death; however, the impact of the coronavirus disease 2019 (COVID-19) lockdown strategy on physical activity (PA) remains unclear. This study compared PA-i.e., daily occupation, transportation to and from daily occupation, leisure time activities, and regular sporting activities-prior (PRE) and during (POST) the on-going COVID-19 outbreak in the Greece lockdown environment. A Greek version of the web-based Active-Q questionnaire was used to access PA. The questionnaire was filled out twice (once each for the PRE and POST conditions) by 8495 participants (age = 37.2 ± 0.2 years (95% confidence interval (CI), 36.9-37.5); males = 38.3% (95%CI, 36.7-40.0); females = 61.7% (95%CI, 60.4-63.0). The relative frequency of overall sporting activities, which, prior to lockdown, occurred at least once per month, and overall participation in competitive sports was significantly reduced (8.6% (95%CI, 7.9-9.3) and 84.7% (95%CI, 82.9-86.6) respectively). With the exception of overall leisure time activities, which were significantly increased in the POST condition, daily occupational, transportation, and sporting activities significant reduced (p < 0.05). Overall PA was reduced in all genders, age, body mass index (BMI) and PA level subgroups in the POST condition, and an interaction between the males and High PA subgroups was observed. The change in overall PA (from PRE to POST conditions) was −16.3% (95%CI, −17.3 to −15.4), while in daily occupational, transportation, and sporting activities, it was −52.9% (95%CI, −54.8-51.0), −41.1% (95%CI, −42.8-39.5) and −23.9% (95%CI, −25.1-22.8), respectively. Thus, the lockdown period is highly associated with a negative change in overall PA. During lockdown, inactivity increased dramatically, with males and the high PA population affected significantly more. The decline in PA is a great concern due to possible long-term consequences on public health and healthcare system.